African American young girls and women in preK12 schools and beyond : informing research, policy, and practice - Mayes, Renae D.; Shavers, Marjorie C.; Moore, James L., III (Emerald Publishing Limited, 2022)
African American Young Girls and Women in PreK12 Schools and Beyond presents a comprehensive viewpoint on preK-12 schooling for African American females. Including theoretical, conceptual, and research based chapters, this volume offers readers compelling evidence of the educational challenges and successes for this student population. The expert authors in this collection provide rich perspectives on the experiences of African American females throughout their elementary and secondary education. Each chapter includes strong implications for education research, practice, and policy, as well as concrete recommendations to important stakeholders, such as educators, school counsellors, and parents. Collectively, the contributors communicate throughout that educational change is needed and that educational success is attainable for all African American females. It is intended that this work will help inform education research, practice, and policy as they relate to African American females. Equally important, it is envisioned that the readers will develop a greater interest in the education of African American females.
Keywords: Girls -- Education.; Women, Black -- Education.; Multicultural education.; Education -- Multicultural Education.; elektronické knihy; electronic books